Effectiveness of combined therapy for patients with brain metastasis - A. G. Chyzh; A. G. Zhukovets; P. D. Demeshko; Yu. N. Grachev; S. L. Polyakov (Опухоли головы и шеи)
Introduction. Incidence of brain metastases rises in recent years. Local control after surgical resection of brain metastases is a priority for patients with limited intracranial disease and controlled primary tumor. Surgery should be combined with other methods because of the high risk of local recurrences.Aim. To analyze the overall survival (OS) and influencing factors for patients with brain metastasis after combined therapy. Materials and methods. The retrospective study included 196 patients with stable systemic cancer or available systemic therapy in cases of progressive disease. All patients had from 1 to 3 brain metastasis. Overall survival and influencing factors after surgical and combined therapy were analysed.Results. Median OS for the entire cohort was 16.9 months. The highest levels of OS were achieved for patients with renal cancer (median OS 32.5 months). For patients with non-small cell lung cancer, breast cancer, melanoma and other cancers OS were 18.8; 19.9; 11.0 and 15.3 months, appropriately. Age, continuation of local therapy in brain (surgical intervention, stereotactic radiosurgery), using of the cisplatin for patients with non-small lung cancer brain metastasis were independent factors that have influenced OS.Conclusion. Application of combined therapy for brain metastasis can provide reasonable OS for patients with controlled systemic disease. Using of the cisplatin as a part of combined therapy provide statistically meaningful rise in OS for patients with non-small lung cancer brain metastasis.